Teseng: A Symbiosis of Law and Local Wisdom in Agricultural Profit-Sharing Agreements in South Sulawesi - Nurdin, Nurdin; Djuniarti, Djuniarti (Jurnal Hukum IUS QUIA IUSTUM, 2026)
This paper explores teseng from the perspective of the symbiosis of law and local wisdom in agricultural sharecropping agreements in South Sulawesi. The aim of this research is to analyse the meaning and practice of teseng in South Sulawesi society, the integration of national legal norms with local wisdom in teseng agreements, and teseng in the context of modernisation and land regulation. The urgency of this research is to look into how teseng works, which mixes government laws and local traditions in farming profit-sharing agreements, helping to create fairness and resolve land disputes in South Sulawesi, where people still strongly follow their customs and local values. This research is a normative legal study with sources of primary and secondary legal materials. The research results show that the meaning and practice of teseng in South Sulawesi society represent a form of local wisdom that emphasises the principles of mutual trust and cooperation between landowners and cultivators, where the division of agricultural produce is carried out naturally based on mutual agreement without a written contract, thus demanding honesty and commitment from both parties. Teseng is not just an economic agreement; it is also part of a long-standing tradition that emphasises social values. In the context of integrating national legal norms, teseng reflects the harmonisation between formal state rules and customary values, which is important for providing legal protection without neglecting social and cultural values while also encouraging written documentation to reduce potential conflicts. Despite facing the challenges of modernisation and land regulations, the teseng system remains relevant and adaptive to economic needs and legal certainty, as long as there is an effort to harmonise local values, economy, and law to ensure fairness and sustainability in the era of change.